Serological Follow‐up of Tuberculosis in a Wild Boar Population in Contact with Infected Cattle. Issue 1 (6th May 2015) - Pérez de Val, B.; Napp, S.; Velarde, R.; Lavín, S.; Cervera, Z.; Singh, M.; Allepuz, A.; Mentaberre, G.
Summary: There is an increasing concern in several European countries over the role that tuberculosis (TB)‐infected wild boar may play in the progress of bovine TB eradication campaigns. In 2004, as a consequence of the detection of a TB focus in wild boar from a National Game Reserve (NGR) located in southern Catalonia, a surveillance programme based on post‐mortem inspection for detection of macroscopic TB‐like lesions (TBLL) was initiated in the affected area. The source of infection for wild boar was linked to a tuberculous cattle herd located in the same area. Besides, the results of the surveillance programme in wild boar were used for the validation of an indirect enzyme‐linked immunosorbent assay (ELISA) specific for Mycobacterium tuberculosis complex (MTBC) IgG antibodies. Using this ELISA, a seven‐year serological study of MTBC in wild boar from the NGR was conducted in 173 animals (93 adults, 44 juveniles–yearlings and 36 piglets) culled between 2004 and 2010. ELISA results and presence of TBLL showed excellent agreement for adult and juvenile wild boar (Kappa index = 0.85; 95% CI: 0.76–0.95). Of the thirty‐eight adults, yearlings and juveniles classified as positives by the ELISA, 34 (89%) showed TBLL at necropsy. In contrast, none of the ELISA‐positive wild boar piglets ( n = 20) showed TBLL, suggesting the detection of early antibody responses to the infection. Overall, this study contributes to the knowledge of wild boar humoral responses to MTBC. The results also highlight the usefulness of this serological test for wild boar TB surveillance.